The Treasury Stock Method and Conventional Method in Reciprocal Stockholdings – An Amalgamation. - Petri, Enrico; Minch, Roland (The Accounting Review, 1974)
Presents information on a study which analyzed the traditional treasury stock method in reciprocal stock holding situations. Explanation on the concept of reciprocal stock holding; Analysis of conventional treatment of mutual stock investments; Methods of allocation by simultaneous equations; Description of an equitable approach to allocation.